A critical phenomenological investigation in the use of touch as “know how” in practical physiotherapy in primary care with children and adults - Bjorbækmo, Wenche Schrøder; Mengshoel, Anne Marit (Frontiers in Rehabilitation Sciences, 2022)
In this article, we examine the interactions between physiotherapists and patients in actual situations, focusing on how touch is expressed, what it may mean and how physiotherapists know (or do not know) when and how to touch. The empirical material is obtained from two Norwegian research projects. In both of them, the first author observed physiotherapeutic practice and conducted interviews with patients (children and adults) and physiotherapists. A phenomenological research approach was applied, and analysis of the empirical data was guided by the concept of bridling, implying adopting a questioning attitude and being open to that which presents itself and exploring its possibilities. Three processed excerpts from the empirical data are presented to illustrate how, in different ways, physiotherapists’ expert knowledge about how to relate to and interact with individual patients is put into play and expressed in real physiotherapy encounters. Each excerpt is presented individually, followed by analysis. Our findings reveal aspects of the epistemology of physiotherapeutic practice to be intercorporal and illuminated by the concept and phenomenon of letting the other be.